PENGARUH MEDIA CANVA TERHADAP MOTIVASI BELAJAR SISWA KEL V SEKOLAH DASAR NEGERI CIBEUNTEUR - Mariana, Siti; Nurhasanah, Siti; Ikmal Amanah, Ramli; Sugiri, Atot (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning motivation of students during the learning process in elementary schools. The study aims to determine the effect of using Canva media on the learning motivation of fifth-grade students at Cibeunteur State Elementary School. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The sample consisted of two groups, namely the experimental group and the control group, with 20 students in each group. The research instrument was a student learning motivation questionnaire. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and hypothesis testing through the Wilcoxon Signed Ranks Test and Mann-Whitney U Test because the data were not entirely normally distributed. The findings revealed that the average learning motivation score of the experimental group increased from 51.85 in the pretest to 97.95 in the posttest, representing an increase of 46.10 points. In contrast, the control group showed only a slight increase from 53.00 to 53.10. The Wilcoxon Signed Ranks Test produced a significance value of 0.000 (< 0.05) for the experimental group, indicating a significant improvement in learning motivation after the implementation of Canva media. Meanwhile, the control group obtained a significance value of 0.597 (> 0.05), indicating no significant improvement. Furthermore, the Mann-Whitney U Test resulted in an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), confirming a significant effect of Canva media on the learning motivation of fifth-grade students at Cibeunteur State Elementary School.